Pengembangan Media Scrapbook Untuk Meningkatkan Kemampuan Membaca Pada Siswa Autis Di SDN Lemah Putro 1 - Nafilah, Lailatun; Wibowo, Satrio; Dewi, Galuh Kartika (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This study aims to test the feasibility of scrapbook media and to improve reading skills in students with autism spectrum at SDN Lemah Putro 1. The development of scrapbook media was validated by two experts: one media expert conducted by an expert lecturer and one material expert conducted by the head of the special assistant teacher. This research uses the development method (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) with the aim of testing the feasibility of the product. There are two data collection methods: validation sheets and tests (pretest and posttest). The results of media validation resulted in 92% data categorized as "Very Feasible", and the results of material validation resulted in 72% data categorized as "Feasible" to use. The pre- and post-test results of each student produced different scores, including Mg 1.3, Df 1.6, Rz 1.4 from these results the scrapbook media is categorized as "High" that there is an increase in reading ability. The result of the research is that scrapbook media is very feasible to use and improve reading skills in autistic students at SDN Lemah Putro 1.